Teoría general de los Derechos Fundamentales : repertorio bibliográfico - Valvidares Suárez, María (Teoría y Realidad Constitucional, 2007)
In this dossier is presented a bibliographical list of some works on general theory of civil liberties and fundamental rights. The list includes not only Spanish works but also scholarship contributions to the subject of other legal systems. In order to classify all the entries, it has been opted to employ an approach by categories, using the basic guidelines formulated by the German scholarship